Job Satisfaction and Employee Performance of Female Bank Employees: Case of Limassol Turkish Cooperative - Poor, Fatemeh Noori (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
This thesis develops a model to evaluate the role of job satisfaction in banking industry among female employees considering high working hours and pressure on bankers. This study investigated mediating role of female job satisfaction between personal attitude and job motivation on bank employees’ job performance in North Cyprus as the study setting. Personal attitude can affect their understanding and expectation of work environment. Motivation is the internal or external stimulus that can increase the individual’s interest to participate completely a process. Job performance is activity that the employee is expected to perform alongside of organization goals. This study evaluates the relationship which has been in marketing management literature to help the managers identify how to increase their employees’ productivity in global competitive market. A total number of 250 bankers participated in the study survey. The result of the study revealed that motivating employees positively influence on their job satisfaction and job performance. and job performance function as a full mediator on relationship between job motivation and job performance. This study at the end finalized with managerial implication and future insights. Key Words: Female, job satisfaction, bank, Northern Cyprus.

ÖZ: Bu çalışma bankacılar üzerindeki baskıyı ve yüksek çalışma saatlerini göz önünde bulundurarak bankacılık sektöründe kadın iş memnuniyetinin rolünü azaltmak için araştırma ve değerlendirmek için yapılmıştır. Bu çalışma kadın iş memnuniyetini kişisel tutum ve çalışmaya yön veren, Kuzey Kıbrıs Türk Cumhuriyetinde hizmet gösteren banka çalışanlarının iş performansının, iş motivasyonuna etkisini incelemiştir. Çalışmamız, literatürde eksikliği olan banka çalışanlarındaki verimliliğin nasıl arttırılabileceği konusunda yardımcı olacaktır. Kişisel tutum, çalışanların kişisel bakış açısı şeklinde onların çalışma ortamı anlayışını ve beklentilerini etkileyebilmektedir. Bu çalışmanın sonucunda, pazarlama literatürüne yeni anlayışlar eklemiş ve ampirik araştırmanın güvenilirliğini kanıtlamıştır. Anahtar Kelimeler: Kadın, iş tatmini, banka, Kuzey Kıbrıs Türk Cumhuriyeti.
Master of Arts in Marketing Management. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2014. Supervisor: Assoc. Prof. Dr. Mustafa Tümer.
Keywords: Business Administration; Marketing Management; Banks and Banking - Cyprus, North; Women employees - Banking Sector - Cyprus, North; Female; job satisfaction; bank; Northern Cyprus